HIV subtype diversity worldwide - Bbosa, Nicholas; Ssemwanga, Deogratius; Kaleebu, Pontiano (Current Opinion in HIV and AIDS, 2019)
To provide a summary of the current data on the global HIV subtype diversity and distribution by region. HIV is one of the most genetically diverse pathogens due to its high-mutation and recombination rates, large population size and rapid replication rate. This rapid evolutionary process has resulted in several HIV subtypes that are heterogeneously globally distributed. Recent findings Subtype A remains the most prevalent strain in parts of East Africa, Russia and former Soviet Union countries; subtype B in Europe, Americas and Oceania; subtype C in Southern Africa and India; CRF01_AE in Asia and CRF02_AG in Western Africa. Recent studies based on near full-length genome sequencing highlighted the growing importance of recombinant variants and subtype C viruses. The dynamic change in HIV subtype distribution presents future challenges for diagnosis, treatment and vaccine design and development. An increase in recombinant viruses suggests that coinfection and superinfection by divergent HIV strains has become more common necessitating continuous surveillance to keep track of the viral diversity. Cheaper near full-length genome sequencing approaches are critical in improving HIV subtype estimations. However, missing subtype data and low sequence sampling levels are still a challenge in some geographical regions.
Keywords: Diversity; HIV; Subtype